THE RIGHT USE OF GROWING MEDIA FOR KENARI (CANARIUM AMBOINENSE HOCH) NURSERIES IN HATUSUA VILLAGE, KAIRATU DISTRICT, WEST SERAM REGENCY, MALUKU PROVINCE - Filiph Tetelay, Febian; Komul, Yulianus Dominggus (LPPM Univ. Ibn Khaldun Bogor, 2022)
Kenari (Canarium Amboinense Hoch) is one type of multipurpose forestry plant. This species has many benefits because, in addition to the fruit produced, wood, leaves, and sap from the Kenari plant (Canarium Amboinense Hoch) can be managed by the community to generate income because it has a fairly high economic value. The main problem faced in the development of the Kenari (Canarium Amboinense Hoch) plant is the correct cultivation process and mechanism and produces quality seeds. The type of Kenari (Canarium Amboinense Hoch) is known to have low dormancy and germination (Jumria, 2011) causing considerable failure in breeding. Another problem faced by farmers in the development of this type is the economic prospect that has not been seen if its cultivation is carried out, especially in West Seram Regency. The main purpose of the service activity is to provide knowledge and understanding to the people of Hatusua Village regarding the cultivation/nursery technique of Kenari (Canarium Amboinense Hoch) through the use of appropriate growing media to produce quality Kenari seeds (Canarium Amboinense Hoch), economic value and conservation value for the environment. The service activity was carried out at the location of the Hatusua State Seed Source Demplot, Kairatu District, West Seram Regency on 8 – 9 April 2022.